Samuel Johnson and the culture of property - Hart, Kevin, 1954- (Cambridge University Press, 1999)
Kevin Hart traces the vast literary legacy and reputation of Samuel Johnson. Through detailed analyses of the biographers and critics who preserved Johnson's life for posterity, Hart explores the emergence of 'The Age of Johnson', and demonstrates how Johnson came to occupy a central place in the English literary canon.